2018
DOI: 10.1002/hon.2566
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy followed by allogeneic HCT versus upfront allogeneic HCT for advanced myelodysplastic syndrome: A propensity score matched analysis

Abstract: To reduce post‐transplant relapse, acute myeloid leukemia (AML) type remission induction chemotherapy has been attempted to reduce disease burden before allogeneic hematopoietic cell transplantation (HCT) in patients with advanced myelodysplastic syndrome (MDS). However, the efficacy of induction chemotherapy before HCT is unclear. We retrospectively analyzed the Japanese registration data of 605 adult patients, who had received allogeneic HCT for advanced MDS between 2001 and 2016, to compare the post‐transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…All these findings challenge a recent recommendation of cytoreduction for patients with > 10% BM blasts [1]. In addition, regardless of the pre‐HSCT cytoreduction strategy (i.e., IC and/or HMA) or regimen, the RFS rate in the present study was relatively higher than the reported 3‐year RFS rates approximately 40% (range, 36.6%‐41.0%) [1114, 25]. The reasons for the difference may be the younger patient age, the lower proportion of patients with CK/MK, and the homogenous myeloablative conditioning regimen in the current cohort compared with those in previous reports [1114, 25].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…All these findings challenge a recent recommendation of cytoreduction for patients with > 10% BM blasts [1]. In addition, regardless of the pre‐HSCT cytoreduction strategy (i.e., IC and/or HMA) or regimen, the RFS rate in the present study was relatively higher than the reported 3‐year RFS rates approximately 40% (range, 36.6%‐41.0%) [1114, 25]. The reasons for the difference may be the younger patient age, the lower proportion of patients with CK/MK, and the homogenous myeloablative conditioning regimen in the current cohort compared with those in previous reports [1114, 25].…”
Section: Discussioncontrasting
confidence: 73%
“…The role of pre‐HSCT cytoreduction either with AML‐like IC or HMA in patients with advanced MDS is still uncertain because of the paucity of randomized trials. Previously published patient populations were highly heterogeneous regarding disease stage, IPSS or IPSS‐R risk stage, or conditioning intensity and were recruited during a period of more than 10 years [1114, 25,26], thereby hindering a direct comparison. Our results, which were proven in multivariate analysis, the PSM dataset analysis, and subgroup analyses, support that pre‐HSCT cytoreduction has comparable outcomes with BSC [27].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the main change in clinical practice during the study period has been the introduction of azacytidine since 2011 in Japan. However, consistent with previous studies, 5,6 our study showed that the relapse rates and mortality did not improve in high-risk patients who received pre-transplant induction chemotherapy and hypomethylating agents compared to those who did not receive them, regardless of transplant year (Figure S2). This may reflect the selection bias that derives from the inclusion of patients with advanced diseases who received pre-transplant induction chemotherapy and hypomethylating agents.…”
supporting
confidence: 91%
“…Among the patients who underwent allo-SCT, the allo-SCT without BRT group also had signi cantly better OS and PFS in comparison to the AZA and CCT groups. Most previous studies compared upfront allo-SCT and BRT with CCT, but none clearly showed the bene ts of CCT before allo-SCT (13,(17)(18)(19)(20)(21). Few studies have compared AZA as a BRT to upfront allo-SCT, and the bene ts AZA before allo-SCT are unknown (19).…”
Section: Discussionmentioning
confidence: 99%